The Influence of Service Quality, Location and Facilities on Customer Satisfaction at Habibs Beauty Botania Batam - Maria; Yossi Hendriati (Indonesian Journal of Economic & Management Sciences, 2023)
This research assesses the impact of service quality, facilities, and location on customer satisfaction at Habibs Beauty Botania Batam. In this study, a quantitative method. Based on the sample in this study, there were 96 respondents. The service quality variable has no effect on customer satisfaction with a tcount value (-0.266) < t table (1.661), the location variable affects customer satisfaction with a tcount (4.011) > t table (1.661). The facility variable has no effect on customer satisfaction with a tcount value (1.619) < t table (1.661), and the variables of service quality, location, and facilities have a simultaneous and significant effect by showing the results of the calculation of Fcount (6,161) > Ftable (2,704)